Implementation of Literacy Culture at SD Negeri 173320 Siborutorop through The Kampus Mengajar Batch 3 Program - Amanda Sela Nathania Marbun; Ernawati Tampubolon; Febrina S.L. Lumbantobing; Yen Aryni; Renta Hutasoit (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2022)
Kampus Mengajar is one of the independent campus programs designed by the Ministry of Education, Culture, Research and Technology. In its implementation, this program provides a mandate for students to be able to carry out learning to students who focus on understanding literacy and numeracy. The main objective of the Kampus Mengajar program is to provide opportunities for students to learn and develop themselves through activities outside the lecture class, helping schools to provide optimal educational services to all students in limited and critical conditions during the pandemic. In addition, the schools that are the target locations of the Kampus Mengajar Program are schools that are still underdeveloped in the aspects of literacy and numeracy, technology adaptation, and administration, therefore students who participate in the Kampus Mengajar Program will greatly assist in the learning process in schools that are still lagging behind in these 4 aspects, one of which is SD Negeri 173320 Siborutorop where with this Kampus Mengajar program, students' literacy skills are really developing.